2009
DOI: 10.1111/j.1744-6171.2009.00177.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Two Types of Social Support for Mothers of Mentally Ill Children

Abstract: PROBLEM-The purpose of this analysis was to compare social support offered by two telehealth nursing interventions for mothers of children with serious mental illnesses. METHODS-A randomized, controlled, quantitative investigation is underway to test two support interventions, using the telephone (TSS) or Internet (WEB).Qualitative description was used to analyze data generated during telehealth interventions. FINDINGS-The behaviors and attitudes of children were challenging for the mothers to manage. Mothers'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 44 publications
4
25
1
2
Order By: Relevance
“…Evidence of instrumental informal information sharing such as using other mothers' experiences as a frame of reference was found as well as formal information sharing such as posting expert or professional resources. Another study similarly identified emotional support, tangible aid, and information as three types of support that parents found online (Scharer et al, 2009). Based on this evidence, in the current study, parents' information seeking and social activities on the Internet will be conceptualized as online resources.…”
Section: Theoretical Frameworkmentioning
confidence: 91%
See 1 more Smart Citation
“…Evidence of instrumental informal information sharing such as using other mothers' experiences as a frame of reference was found as well as formal information sharing such as posting expert or professional resources. Another study similarly identified emotional support, tangible aid, and information as three types of support that parents found online (Scharer et al, 2009). Based on this evidence, in the current study, parents' information seeking and social activities on the Internet will be conceptualized as online resources.…”
Section: Theoretical Frameworkmentioning
confidence: 91%
“…The Internet can be conceptualized as an online ecology, supplying families with needed resources such as information found on parenting websites or social support found in online forums (Martin & Robinson, 2007;Walker & Greenhow, 2010). Several descriptive studies have found that discussion boards, parenting websites, and blogs were useful contexts for parents and provided a virtual space for parents to connect and support one another (Drentea & Moren-Cross, 2005;Madge & O'Connor, 2006;McDaniel, Coyne & Holmes, 2011;Miyata, 2002;Scharer et al, 2009). A systems approach also implies that children will benefit when parents find resources online (Brady & Guerin, 2010).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…[231][232][233][234]239,248 The majority of studies were conducted in the USA (17 studies 230,231,234,236,[238][239][240][241][242][243][244]246,248,255 ); other main locations were Australia (three studies 227,228,235 ), the Netherlands (three studies 245,247,249 ), Sweden (three studies 233,237,250 ) and the UK (two studies 232,256 ).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…However, as authors may have described similar technologies using different names, there may be some overlap between categories. Videoconferencing or video consultation was the most frequently used tool (14 studies 227,228,233,235,236,238,[240][241][242][243][244]246,248,253 ), followed by e-mails or web messaging systems (13 studies 223,[229][230][231][232]234,[237][238][239]245,247,249,250,254,256 ). Other categories were web chat (two studies 239,255 ) and SMSs (one study 224 ).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation